The Reduce, Reuse, dan Recycle (3R) sebagai Solusi terhadap Bahaya Banjir di Sekitas TPSS Kaliwates - Hikamah, Siti Roudlotul; ., Sumiati; Agustin, Renita; Maulana, Ilham; Rozikin, Moch. Khoirur (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2024)
Indonesia faces various problems, including those related to waste management. Large amounts of waste have a negative impact on environmental health. Kaliwates Subdistrict has problems related to waste, because residents in this area are still not able to manage waste properly. They still like to throw garbage around the river, even though there is a waste processing site. The service is carried out using the ABCD method. Efforts are being made to minimize the amount of waste by implementing reuse, reduce, and recycle (3R). This service activity can increase public knowledge and awareness to reduce the accumulation of waste, namely through the habit of reusing used bottles, reducing the use of plastic by shopping with bags or baskets from home. In this activity, the community followed and participated enthusiastically so that they began to be aware of implementing 3R in their homes and creating an environment around the river with minimal waste, and creating a healthy environment, and waste having economic value.